2015
DOI: 10.1007/s10008-015-3012-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics, stress, and Stefan-Maxwell diffusion in solids: application to small-strain materials used in commercial lithium-ion batteries

Abstract: The life and performance of lithium-ion batteries are related to the mechanical expansion and contraction of the active materials. We develop a theory and commensurate equations to describe how lithium diffuses within host materials; our focus is clarifying the influence of stress on solidstate diffusion processes. Small-strain mechanics are combined with diffusion processes described by the StefanMaxwell equations. For the first time, to our knowledge, we compare host materials in which (a) both the host and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…12, and multi-species transport entails multiple diffusion coefficients such as, for example, the binary diffusion coefficients appearing in the Stefan-Maxwell equations. 2,16 The precise nature of lithium transport in host materials is still the subject of ongoing research, but in Ref. 7 it was observed that diffusion in graphite associated with PITT measurements in Ref.…”
Section: Theory For the Equilibrium Thermodynamicsmentioning
confidence: 99%
“…12, and multi-species transport entails multiple diffusion coefficients such as, for example, the binary diffusion coefficients appearing in the Stefan-Maxwell equations. 2,16 The precise nature of lithium transport in host materials is still the subject of ongoing research, but in Ref. 7 it was observed that diffusion in graphite associated with PITT measurements in Ref.…”
Section: Theory For the Equilibrium Thermodynamicsmentioning
confidence: 99%
“…The cause of this apparent increase may be related to the graphite phase change and should be investigated in future work either through a multi-species reaction model [77][78][79][80] or a model that considers particle level stress induced diffusion modifications. 81,82…”
Section: Resultsmentioning
confidence: 99%
“…The lithium flux inside the particle can be determined from the gradient of chemical potential 14 : boldJ=DRTcm()cscm()1cnormalscnormalmμ, where c m is the maximum lithium concentration, and D is the diffusion of lithium inside the particle. From Equations () and (), ∇ μ is the difference of chemical potential between the lithiated sites and vacant sites: μ=()μLinormalθ0μθ0+italicRT()lnaLinormalθlnaθ()ΩLinormalθΩθσh. Since the μLinormalθ0 and μθ0 are the standard state potentials of lithiated sites and non‐lithiated sites, respectively, Equation () can be simplified as follows: μ=italicRT()lnaLinormalθlnaθnormalΩσh. Taking the derivative of Equation () provides: F0.5emEeq0=R0.12emT()lnaLinormalθlnaθ, FEeq0cscs…”
Section: Modelling and Simulation Methodsmentioning
confidence: 99%
“…Yang introduced a mathematical relation between hydrostatic stress and atomic concentration 13 . Recently, stress‐dependent chemical potential has been applied to investigate the chemo‐mechanical behavior of Li‐ion batteries 9,14,15 . Zhang et al used the analogy of thermal stress to study the stress development in a single particle of the electrode 16 .…”
Section: Introductionmentioning
confidence: 99%